A structural basis for IκB kinase 2 activation via oligomerization-dependent trans auto-phosphorylation. - Smarajit Polley (Public Library of Science (PLoS), 2013)
Activation of the IκB kinase (IKK) is central to NF-κB signaling. However, the precise activation mechanism by which catalytic IKK subunits gain the ability to induce NF-κB transcriptional activity is not well understood. Here we report a 4 Å x-ray crystal structure of human IKK2 (hIKK2) in its catalytically active conformation. The hIKK2 domain architecture closely resembles that of Xenopus IKK2 (xIKK2). However, whereas inactivated xIKK2 displays a closed dimeric structure, hIKK2 dimers adopt open conformations that permit higher order oligomerization within the crystal. Reversible oligomerization of hIKK2 dimers is observed in solution. Mutagenesis confirms that two of the surfaces that mediate oligomerization within the crystal are also critical for the process of hIKK2 activation in cells. We propose that IKK2 dimers transiently associate with one another through these interaction surfaces to promote trans auto-phosphorylation as part of their mechanism of activation. This structure-based model supports recently published structural data that implicate strand exchange as part of a mechanism for IKK2 activation via trans auto-phosphorylation. Moreover, oligomerization through the interfaces identified in this study and subsequent trans auto-phosphorylation account for the rapid amplification of IKK2 phosphorylation observed even in the absence of any upstream kinase.